PHD THESIS SUMMARY: Otto Neurath and Ludwig von Mises: Philosophy, Politics, and Economics in Viennese Late Enlightenment - Linsbichler, Alexander (Erasmus journal for philosophy and economics, 2021)
Logical empiricism and the Austrian School of economics are two of the internationally most influential intellectual movements with Viennese roots. By and large independently of each other, both have been subject to detailed historical and philosophical investigations for the last two decades. However, in spite of numerous connections and interactions between the two groups, their relationship has captured surprisingly sparse attention. Here, Linsbichler focuses on the many-faceted juxtaposition of two supposedly antagonistic champions of Viennese Late Enlightenment: logical empiricist Otto Neurath and Austrian economist Ludwig Mises.